1976
DOI: 10.1126/science.181841
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Tolerance to a Specific Effect of Ethanol on Posttetanic Potentiation in Aplysia

Abstract: Perfusion with 0.8 molar ethanol in a seawater specifically accelerates the rate of decay of posttetanic potentiation observed after repetitive electrical stimulation of an identified synapse in the abdominal ganglion of Aplysia californica. Repeated perfusion with seawater alternately with and without ethanol leads to a progressive diminution of this specific effect of ethanol, such that after the third application ethanol no longer has any effect on the rate constant of decay of posttetanic poteniation. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 7 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…For example, chronic exposure to EtOH has been shown to disrupt long‐term potentiation (LTP) in the hippocampus (reviewed in Zorumski et al., ) and lateral amygdala (Stephens et al., ) and has been shown to produce LTP‐like effects through presynaptic and postsynaptic mechanisms in the BLA (Christian et al., , ; Läck et al., ). Furthermore, chronic exposure has also been shown to modulate short‐term plasticity including paired‐pulse facilitation at both glutamatergic and GABAergic synapses (reviewed in McCool, ) as well as the magnitude and duration of PTP (Gage and Hubbard, ; Traynor et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, chronic exposure to EtOH has been shown to disrupt long‐term potentiation (LTP) in the hippocampus (reviewed in Zorumski et al., ) and lateral amygdala (Stephens et al., ) and has been shown to produce LTP‐like effects through presynaptic and postsynaptic mechanisms in the BLA (Christian et al., , ; Läck et al., ). Furthermore, chronic exposure has also been shown to modulate short‐term plasticity including paired‐pulse facilitation at both glutamatergic and GABAergic synapses (reviewed in McCool, ) as well as the magnitude and duration of PTP (Gage and Hubbard, ; Traynor et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…There have also been reports of tolerance occurring without any signs of physical dependence. For example, Traynor, Woodson, Schlapfer, and Barondes (1976) found that several hours of intermittent ethanol exposure produced tolerance to ethanol's effect on the decay of posttetanic potentiation in the abdominal ganglion of Aplysia but that no abnormality was evident in the tissue after the cessation of ethanol exposure. In addition, Mana and Pinel (1987) reported that amygdala-kindled rats that were made tolerant to ethanol's anticonvulsant effect displayed no evidence of an increase in the duration of elicited seizures when ethanol was completely withdrawn.…”
Section: Discussionmentioning
confidence: 99%